NURSING EXERCISE IN PATIENTS ADMITTED BY RECENTLY DECOMPENSATED HEART FAILURE - THE ERIC PROGRAM - Bruno Delgado; Ivo Lopes; Eugénia Mendes; Bárbara Gomes; André Novo; Leonel Preto (Revista Portuguesa de Enfermagem de Reabilitação, 2018)
Background: Heart failure (HF) promomtes limitations on the activities of daily living and consequent loss of functional and instrumental autonomy. It represents one of the most concerning health problems due to its significant economic impact.